Synthesis, Characterization and Antimicrobial Evaluation for New Esters Derivatives Containing Two 1, 3, 4-Oxadiazole Units - Hamdan, Israa Abd Al-Hasan; Tomma, Jumbad H. (Iraqi Journal of Science, 2024)
This work includes the synthesis of new ester compounds containing two 1,3,4-oxadiazole rings, 15a-c and 16a-c. This was done over seven steps, starting with p-acetamido-phenol 1 and 2-mercaptobenzoimidazole 2. The structure of the products was determined using FT-IR, 1H NMR, and mass spectroscopy. The evaluation of the antimicrobial activities of some prepared compounds was achieved against four types of bacteria (two types of gram-positive bacteria; Staphylococcus aureus and Bacillus subtilis, and two types of gram-negative bacteria, Pseudomonas aeruginosa and E. Coli), as well as against one types of fungus (C. albino). The results show moderate activit against the study bacteria, and the theoretical analysis of the toxicity demonstrates non-toxicity with acute oral human toxicity. Also, the toxicity of these compounds in rats was weak. A molecular modelling study explains that these compounds possess good binding with lung cancer proteins.